A Rejoinder to a Contemporary Non-Economist: A Comment on a Comment - Kapeliushnikov Rostislav (Journal of Economic Sociology, 2019)
The article is a rejoinder to a critical assessment of Kapeliushnikov’s study on discursive methods used by M. Weber in The Protestant Ethics and the Spirit of Capitalism that was provided by Ivan Zabaev in his recently published article, “A Nietzschean Take on a Hundred-Dollar Bill: Reading Weber’s ‘Protestant Ethic’: in Connection with a Contemporary Economist’s Comments.” Kapeliushnikov demonstrates that Zabaev’s attempt to view The Protestant Ethics and the Spirit of Capitalism as a treatise on ethics rather than as a scientific study is not justified, and that Weber himself would hardly approve such a moralistic approach. The tendency to substitute a substantive discussion for a manipulation with words is also without merit. For instance, Zabaev’s suggestion that for Weber the German words Gewinn and Erwerb had a diametrically opposite sense is quite absurd. Kapeliushnikov’s commentary pays special attention to Zabaev’s attempts to interpret Weber’s study through a lens of Nietzschean ideas. Paradoxically, this approach has led Zabaev to unequivocally anti-Weberian conclusions. In particular, this Nietzschean interpretation of a famous metaphor of “a steel shell” gets a meaning that is completely at variance with its original conception. Kapeliushnikov concludes that a traditional approach when The Protestant Ethics and the Spirit of Capitalism is seen as a study on economic history or historical sociology rather than as a treatise on ethics is more correct and does not engender numerous aberrations that Zabaev was not capable of avoiding.